React's Evolution and the Paradigm Shift of Hooks in Modern Web Development - Reddy Goli, Vishnuvardhan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The component-based framework within React devised a new approach to frontend development that enabled better code reuse alongside simplified maintenance procedures. Virtual DOM by React established itself as a library leader by minimizing browser communication because of its performance benefits. The Hooks feature from version 16.8 marked the most significant evolutionary addition, allowing functional components to independently manage both state and side effects without class components. Introducing Hooks like useState and useEffect brought state management improvements that produced more condensed and easier-to-understand code. This article investigates React’s development trajectory, the critical role of virtual DOM, and the fundamental changes from Hooks to modern web application development. The article explores distinct aspects to show how Hooks now controls software development methods and helps programmers use functional code practices to boost application performance.